Refoldable Foldamers: Global Conformational Switching by Deletion or Insertion of a Single Hydrogen Bond. (14th January 2016) - Le Bailly, Bryden A. F.; Byrne, Liam; Clayden, Jonathan
Abstract: Small changes in the structure of a foldamer may lead to gross changes in conformational preference. We show that the simple insertion or deletion of a single hydrogen bond by changes in pH or by photochemical deprotection is sufficient to refold a helical oligomer, interconverting M and P screw‐sense preference. As a consequence of the switch, information may be transmitted to a remote catalytic site, selectively directing the formation of either of two enantiomeric products by a reaction involving 1, 22‐remote intermolecular asymmetric induction.